STRATEGI KOMUNIKASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY DI PT. TELEKOMUNIKASI SELULAR (TELKOMSEL) (STUDI KASUS PADA PROGRAM INTERNET BAIK) - Amalia Nurul; Ayub Ilfandy Imran (Dialektika, 2018)
This study discusses the communication strategy of Corporate Social Responsibility program at PT. Telekomunikasi Selular (Telkomsel). The background of this research is the Internet BAIK program has reached the target of Internet BAIK program up to now has educated 27 cities with 56 schools, 3972 students, 4764 parents, teachers, and community, and 1145 Internet BAIK ambassadors. Internet BAIK Program won an award from MIX Marketing Communication Magazine in the 2017 Best Social Campaign category. This research uses qualitative method with case study approach and using constructivist paradigm. In this study there are four informants that are two key informants and two supporting informants. Based on the results of this study, Telkomsel's CSR communication strategy on the Internet BAIK (Responsible, Safe, Inspirational, and Creative) Internet program that this program has six goals, the target of this program are elementary, junior high, community, teachers, and parents. Submission of the message must be tailored to the target audience and the content of the message relates to the use of the Internet BAIK. The media used are mass media, online media, and social media. The series of activities are radio talkshows, seminars, workshops, and educational classes. There are nine parties who help this Internet BAIK program and the timing of communication execution tailored to calendar and mapping timings. Evaluation is done on every activity, city, and overall. This program does not have a scientific benchmark and the program will continue until 2018. The conclusion is that Telkomsel through this Internet BAIK program uses CSR communication strategy that is aim, objectives, messages, instruments and activities, resources and time scale, series of activities, evaluation, benchmarks of success and sustainability of the program in carrying out its communications activities.